The prognostic role of different renal function phenotypes in patients with acute heart failure. (1st February 2019) - Palazzuoli, Alberto; Ruocco, Gaetano; Pellicori, Pierpaolo; Incampo, Eufemia; Di Tommaso, Cristina; Favilli, Roberto; Evangelista, Isabella; Nuti, Ranuccio; Testani, Jeffrey M.
Abstract: Objective: Worsening renal function (WRF) is common in patients treated for acute heart failure (AHF) and might be associated with a significant increase in blood nitrogen urea (BUN). Although many patients develop WRF during hospitalisation, its prognostic role is still unclear. Thus, we aimed to evaluate the prognostic relevance of WRF according to BUN changes during hospitalization. Methods: We studied patients with AHF screened for Diur-HF Trial (NCT01441245). WRF was defined as an in-hospital rise in serum creatinine ≥0.3 mg/dl or estimated glomerular filtration rate (GFR) reduction ≥20%. BUN increase was defined as a rise in BUN ≥20% during admission. Effective decongestion was defined as complete resolution of two, or more, signs of HF, or absence of clinical signs of congestion at discharge. Results: Of 247 patients enrolled, 59 (23%) patients experienced WRF, 107 (43%) had a BUN increase ≥20%, and 111 (45%) were effectively decongested during hospitalization. During 180 days of follow-up, 136 patients died or were re-hospitalised for AHF. An increase in BUN was an independent predictor of adverse outcome, regardless of WRF (HR = 2.19 [1.35–3.54], p  = 0.002 and 1.71 [1.14–2.59], p  = 0.010; with and without WRF, respectively) or congestion at discharge. WRF was not an independent predictor of outcome if BUN did not increase or when congestion was effectively relieved. Conclusions: an increase in BUN≥20% during hospitalization for AHF predicts a poor outcome independently from renal function deterioration and decongestion. WRF predicts adverse outcome only if BUN increases substantially or clinical congestion persists. Highlights: The prognostic relevance of kidney function in acute heart failure has been investigated with contradictory results. The definition of worsening renal function may be challenged with introduction of blood urea nitrogen evaluation. Worsening renal function defined according BUN could improve CRS type-1 diagnosis and could identify patients at high risk.